2017
DOI: 10.1177/0363546517717679
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Regeneration of Large and Deep Osteochondral Defects of the Knee by Bone Augmentation Combined With Matrix-Guided Autologous Chondrocyte Transplantation

Abstract: Large and deep osteochondral defects of the knee joint can be treated successfully with bone augmentation and MACT. The treatment of shallow bony defects with cancellous bone grafting and deep bony defects with bone block augmentation shows promising results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 39 publications
(82 reference statements)
2
25
0
7
Order By: Relevance
“…The result of the treatment we proposed in this report is comparable to the good results obtained with other types of treatment 10 , 13 , 14 , 17 , 18) . It also has the advantage of not requiring an intra-articular donor site and allografts in cases with deep and large defects greater than 2 cm 2 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The result of the treatment we proposed in this report is comparable to the good results obtained with other types of treatment 10 , 13 , 14 , 17 , 18) . It also has the advantage of not requiring an intra-articular donor site and allografts in cases with deep and large defects greater than 2 cm 2 .…”
Section: Discussionsupporting
confidence: 86%
“…Hohmann and Tetsworth 13) described in patients with OCD over 2.5 cm 2 , the use of a fresh-frozen irradiated allograft provided good results; nevertheless, this type of graft is expensive and unavailable worldwide. Zellner et al 14) reported good outcomes were achieved with use of bone autograft from either the iliac crest or the distal femur, combined with autologous chondrocyte transplantation in large and deep osteochondral defects; however, this also raises costs and is not widely available.…”
Section: Discussionmentioning
confidence: 99%
“…Gobbi et al [ 30 ] reported a long-term and sustained benefit of concentrated bone-marrow aspirate compared to microfracture for the treatment of osteochondral lesions of the knees. Zellner et al [ 31 ] described promising clinical and radiological results, achieving successful bone regeneration of large and deep osteochondral defects of the knee joint after the treatment with concentrated bone-marrow aspirate combined with bone augmentation. In our study, arthroplasty was avoided in all the patients during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“… 40 The combination of MACT using Novocart 3D and bone augmentation even showed a MOCART score of 82.6 at 1 year after treatment. 41 Furthermore, long-term MACT results are available. Aldrian et al 2 examined patients treated using Hyalocraft C (Anika Therapeutics), a hyaluronic acid-based scaffold, after a minimum period of 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not find evidence for a correlation between MRI and clinical outcome scores, which creates doubts about this choice of examination. 2 , 10 , 41 For this purpose, functional (biochemical) MRI, such as delayed gadolinium-enhanced MRI of cartilage, quantitative T1rho, T2-weighted mapping, or chemical exchange saturation transfer on glycosaminoglycans (GagCest), might be more suitable for the evaluation of cartilage repair in concordance with the clinical situation. 39 , 40 However, availability and applicability of these techniques are still limited, and the interpretation is complex and time-consuming.…”
Section: Discussionmentioning
confidence: 99%